Development of android-based apps for courier service management - A. Mohd; R. A. Rashid; A. H. F. Abdul Hamid; M. A. Sarijari; M. R. A. Rahim; H. Sayuti; M. R. Abdul Rashid (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
E-commerce has grown exponentially over the years. The growth has been characterized by strong consumer demands and the increasing number of various products available online. This in turn creates a logistical problem and a high demand for an efficient courier service to support the growing markets. It is very important for courier service provider that the delivery of the parcel is being done as fast as possible. One of the courier service’s vital and most crucial business process is in the last mile parcel delivery. This is where an efficient delivery service will be of utmost importance. An efficient system needs to be developed in order to facilitate the interaction between the courier service provider and consumer to precisely determine the optimal route for the parcel delivery. In this paper, an Android-based application system for courier service management with last mile route tracking module is developed. It is a mobile application that eases the courier delivery personnel in finding their way to deliver the parcels to the customer’s doorstep. The application will guide the courier personnel to get a list of courier data such as address and contact information and then navigate them to the selected customers’ addresses based on traffic data retrieved from Google Maps API. It will choose the best route to the address and notify the customers before arriving so that the customers are ready to receive the parcel. This last mile route tracking for parcel delivery will provide the basis for an efficient courier service system.